Nonlocal Black Hole Evaporation and Quantum Metric Fluctuations via Inhomogeneous Vacuum Density. (8th November 2018) - Yosifov, Alexander Y.; Filipov, Lachezar G.
Abstract : Inhomogeneity of the actual value of the vacuum energy density is considered in a black hole background. We examine the back-reaction of a Schwarzschild black hole to the highly inhomogeneous vacuum density and argue the fluctuations lead to deviations from general relativity in the near-horizon region. In particular, we found that vacuum fluctuations onto the horizon trigger adiabatic release of quantum information, while vacuum fluctuations in the vicinity of the horizon produce potentially observable metric fluctuations of order of the Schwarzschild radius. Consequently, we propose a form of strong nonviolent nonlocality in which we simultaneously get nonlocal release of quantum information and observable metric fluctuations.